2021
DOI: 10.1007/s10896-021-00313-1
|View full text |Cite
|
Sign up to set email alerts
|

"These Questions Have Everything That Happens to me": Analysis of a Femicide Risk Assessment Tool for Abused Women in Brazil

Abstract: Purpose The purpose of this mixed-methods triangulation study was to assess the face validity and comprehension of a femicide risk assessment tool, the Danger Assessment-Brazil (DA-Brazil) among women seeking care in a one stop center for abused women in Curitiba, Brazil. Our secondary aim was to assess professionals' perceptions of feasibility for using the DA-Brazil in the same setting. Method Fifty-five women experiencing relationship violence completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
3
0
1
Order By: Relevance
“…After translation and adaptation, most of the of the items were understood and relevant to the participants, although some challenges were identified which required adaptation of items, wording, and response options. These results are similar and consistent with the literature around linguistic translations and cultural adaptation [31][32][33][34].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…After translation and adaptation, most of the of the items were understood and relevant to the participants, although some challenges were identified which required adaptation of items, wording, and response options. These results are similar and consistent with the literature around linguistic translations and cultural adaptation [31][32][33][34].…”
Section: Discussionsupporting
confidence: 92%
“…Experiences of participants not understanding the meaning of some items during translation and adaptation of measures is common [ 32 , 40 ]. Our study showed similar findings where some participants did not understand some words used in the items.…”
Section: Discussionmentioning
confidence: 99%
“…Specific information about the scale can be consulted in https://www.dangerassessment.org/DA.aspx . There is a recent experience of the use of the danger assessment scale in Brazilian women that show good results (Evans et al, 2022 ). The results of the risk assessment were attached to the medical records of each user to support the actions of the professional who met the particular case and to guide the monitoring according to the level of risk.…”
Section: Methodsmentioning
confidence: 99%
“…Specific information about the scale can be consulted in https://www.dangerassessment.org/DA.aspx . There is a recent experience of the use of the danger assessment scale in Brazilian women that show good results (Evans et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Dessa forma, é evidente a relevância dos aumenta, devem ser enaltecidos e multiplicados nesses espaços (DAWSON; PISCITELLI, 2017).A utilização de ferramentas de análise para avaliar riscos de recorrências de agressões e tentativas de feminicídios nas redes assistenciais e protetivas, seria uma alternativa útil para identificar precocemente as situações de vulnerabilidade(WILLIAMS;STANSFIELD;CAMPBELL, 2022;YOUNGSON et al, 2021). No entanto, proteção da integridade da vítima(EVANS et al, 2021).2.5 "E SE ELAS TIVESSEM DENUNCIADO?" O PAPEL DO ESTADO E OS DESAFIOS DOS SERVIÇOS ASSISTENCIAIS E PROTETIVOS NO TERRITÓRIOO papel do Estado no enfrentamento de violência contra a mulher é reforçado diante do avanço constitucional, em marcos regulatórios e na estruturação de redes intersetoriais (VIGANO;LAFFIN, 2019).…”
unclassified